The Mode-of-Action of Targeted Alpha Therapy Radium-223 as an Enabler for Novel Combinations to Treat Patients with Bone Metastasis - Mari I. Suominen; Timothy Wilson; Sanna-Maria Käkönen; Arne Scholz (MDPI, 2022)
Bone metastasis is a common clinical complication in several cancer types, and it causes a severe reduction in quality of life as well as lowering survival time. Bone metastases proceed through a vicious self-reinforcing cycle that can be osteolytic or osteoblastic in nature. The vicious cycle is characterized by cancer cells residing in bone releasing signal molecules that promote the differentiation of osteoclasts and osteoblasts either directly or indirectly. The increased activity of osteoclasts and osteoblasts then increases bone turnover, which releases growth factors that benefit metastatic cancer cells. In order to improve the prognosis of patients with bone metastases this cycle must be broken. Radium-223 dichloride (radium-223), the first targeted alpha therapy (TAT) approved, is an osteomimetic radionuclide that is incorporated into bone metastases where its high-linear energy transfer alpha radiation disrupts both the activity of bone cells and cancer cells. Therefore, radium-223 treatment has been shown preclinically to directly affect cancer cells in both osteolytic breast cancer and osteoblastic prostate cancer bone metastases as well as to inhibit the differentiation of osteoblasts and osteoclasts. Clinical studies have demonstrated an increase in survival in patients with metastatic castration-resistant prostate cancer. Due to the effectiveness and low toxicity of radium-223, several novel combination treatment strategies are currently eliciting considerable research interest.